Treated Industrial Wastewater Effects on Chemical Constitution Maize Biomass, Physicochemical Soil Properties, and Economic Balance. Issue 3 (4th February 2018) - Carlos, Filipe Selau; Schaffer, Naihana; Andreazza, Robson; Morris, Lawrence A; Tedesco, Marino José; Boechat, Cácio Luiz; Camargo, Flávio Anastácio de Oliveira
ABSTRACT: Irrigation with treated wastewaters can improve nutrient levels and yield of crops planted on degraded soils. This study evaluated how irrigation with treated industrial wastewater affected biomass production and nutrition of maize plants and physio-chemical properties of a degraded soil. The experiment was conducted in a greenhouse using PVC columns. Treatments consisted of 8 treatments irrigated with clean water and increasing doses of N and P, and 8 treatments with 4 proportions of wastewater irrigation (25%, 50%, 75% and 100% v/v). In general, maize biomass did not differ between irrigation water sources. Differences were largely associated with N nutrition. We observed increases in concentrations of N, P, K, S, Mn, Na, Cu, and Zn in tissue of maize under irrigation with wastewater. The addition of treated wastewater increased the P and Na concentrations, and EC values in the soil without affecting clay dispersion in water. An associated economic analysis indicated that wastewater irrigation would not be economically feasible without including environmental benefits. In southern Brazil, the proportion of irrigation water that is wastewater should not exceed 50%.